The centrosomal protein 131 participates in the regulation of mitochondrial apoptosis - Clotilde C. N. Renaud; Kilian Trillet; Jane Jardine; Laura Merlet; Ophélie Renoult; Mélanie Laurent—Blond; Zoé Catinaud; Claire Pecqueur; Julie Gavard; Nicolas Bidère (Communications Biology, 2023)
Abstract Centriolar satellites are multiprotein aggregates that orbit the centrosome and govern centrosome homeostasis and primary cilia formation. In contrast to the scaffold PCM1, which nucleates centriolar satellites and has been linked to microtubule dynamics, autophagy, and intracellular trafficking, the functions of its interactant CEP131 beyond ciliogenesis remain unclear. Using a knockout strategy in a non-ciliary T-cell line, we report that, although dispensable for centriolar satellite assembly, CEP131 participates in optimal tubulin glycylation and polyglutamylation, and microtubule regrowth. Our unsupervised label-free proteomic analysis by quantitative mass spectrometry further uncovered mitochondrial and apoptotic signatures. CEP131-deficient cells showed an elongated mitochondrial network. Upon cell death inducers targeting mitochondria, knockout cells displayed delayed cytochrome c release from mitochondria, subsequent caspase activation, and apoptosis. This mitochondrial permeabilization defect was intrinsic, and replicable in vitro with isolated organelles. These findings extend CEP131 functions to life-and-death decisions and propose ways to interfere with mitochondrial apoptosis.